EXPLORING THE ROLE OF GREEN MARKETING IN SUSTAINABLE BUSINESS PRACTICES - Awari, Nilesh P.; Shah, Swapnil A.; Mahisekar, Devkumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the impact of green marketing on sustainable business practices and explores employee perceptions regarding the implementation of green marketing for sustainability. Utilizing a quantitative approach, data were collected through structured surveys from 189 employees from various industries. The results indicate that green marketing initiatives significantly enhance sustainability practices, environmental performance, and integration into business strategies, while also boosting company reputation and customer loyalty. Employees exhibited strong positive perceptions of green marketing, expressing pride in their company’s sustainability efforts and supporting continued implementation and expansion of these practices. These findings underscore the importance of green marketing as a strategic tool for achieving long-term business success and environmental stewardship. Future research should focus on developing comprehensive models linking green marketing to consumer behaviour and exploring its long-term financial impacts across different sectors and regions.